Characterisation of a peripheral neuropathic component of the rat monoiodoacetate model of osteoarthritis. - Matthew Thakur; Wahida Rahman; Carl Hobbs; Anthony H Dickenson; David L H Bennett (PLoS ONE)
Joint degeneration observed in the rat monoiodoacetate (MIA) model of osteoarthritis shares many histological features with the clinical condition. The accompanying pain phenotype has seen the model widely used to investigate the pathophysiology of osteoarthritis pain, and for preclinical screening of analgesic compounds. We have investigated the pathophysiological sequellae of MIA used at low (1 mg) or high (2 mg) dose. Intra-articular 2 mg MIA induced expression of ATF-3, a sensitive marker for peripheral neuron stress/injury, in small and large diameter DRG cell profiles principally at levels L4 and 5 (levels predominated by neurones innervating the hindpaw) rather than L3. At the 7 day timepoint, ATF-3 signal was significantly smaller in 1 mg MIA treated animals than in the 2 mg treated group. 2 mg, but not 1 mg, intra-articular MIA was also associated with a significant reduction in intra-epidermal nerve fibre density in plantar hindpaw skin, and produced spinal cord dorsal and ventral horn microgliosis. The 2 mg treatment evoked mechanical pain-related hypersensitivity of the hindpaw that was significantly greater than the 1 mg treatment. MIA treatment produced weight bearing asymmetry and cold hypersensitivity which was similar at both doses. Additionally, while pregabalin significantly reduced deep dorsal horn evoked neuronal responses in animals treated with 2 mg MIA, this effect was much reduced or absent in the 1 mg or sham treated groups. These data demonstrate that intra-articular 2 mg MIA not only produces joint degeneration, but also evokes significant axonal injury to DRG cells including those innervating targets outside of the knee joint such as hindpaw skin. This significant neuropathic component needs to be taken into account when interpreting studies using this model, particularly at doses greater than 1 mg MIA.